The Influence of Gestational Age and Birth Weight on Neonatal Mortality - Wedi Iskandar; Yeni Andayani; Lia Marlia; Burhan Burhan; Aris Primadi (Global Medical & Health Communication (GMHC), 2020)
Prematurity and low birth weight are some of the causes of neonatal death and significant health problem. This study aimed to determine the influence of gestational age and birth weight on neonatal mortality at the Al Islam Hospital Bandung in 2015–2019. It was a case-control retrospective observational analysis using medical records of the Al Islam Bandung Hospital from January 1, 2015, to December 31, 2019. The inclusion criteria for infants were born alive. Exclusion criteria had severe congenital abnormalities and gestational age <26 weeks. The chi-square test evaluated the univariate comparison test of risk factors between 2 groups. Multiple logistic regression to assess neonatal mortality's predictive factors and the percentage contribution of the influence was calculated (Nagelkerke’s R2 analysis). The number of infants enrolled in 2015–2019 was 6,791 neonates, and who died was 56 neonates (0.82%). In premature infants and low birth weight there was a very significant relationship with neonatal mortality, respectively p=0.000 (p<0.05) OR=30.397 (CI=16.506–55.976), and p=0.000 (p<0.05) OR=41.206 (CI=18.611–91.233). In the multiple logistic regression test, p=0.000 (p<0.05), with a Nagelkerke’s R2 value of 0.344 or 34.4%. This presence that gestational age and birth weight significantly affects neonatal mortality, either partially or simultaneously. The percentage contribution of the influence of gestational age and birth weight to neonatal mortality was 34.4%. PENGARUH USIA GESTASI DAN BERAT BADAN LAHIR TERHADAP KEMATIAN NEONATUSPrematuritas dan berat badan lahir rendah merupakan beberapa penyebab kematian neonatus dan masalah kesehatan yang signifikan. Penelitian ini bertujuan mengetahui pengaruh usia gestasi dan berat badan lahir terhadap kematian neonatus di RS Al Islam Bandung tahun 2015–2019. Penelitian ini merupakan penelitian observasional retrospektif kasus kontrol menggunakan data rekam medis RS Al Islam Bandung periode 1 Januari 2015 hingga 31 Desember 2019. Kriteria inklusi bayi lahir hidup. Kriteria eksklusi bayi dengan kelainan kongenital berat dan usia gestasi <26 minggu. Uji chi-square mengevaluasi perbandingan univariat faktor risiko antara 2 grup. Regresi logistik multipel untuk mengevaluasi faktor prediktif kematian neonatus dan persentase kontribusi pengaruh dihitung (Analisis R2 Nagelkerke). Jumlah bayi yang dirawat tahun 2015–2019 sebanyak 6.791 dan yang meninggal sebanyak 56 (0,82%). Pada bayi lahir prematur dan berat badan lahir rendah terdapat hubungan sangat bermakna terhadap kematian neonatus, berturut-turut p=0,000 (p<0,05) OR=30,397 (CI=16,506–55,976) dan p=0,000 (p<0,05) OR=41,206 (CI=18,611–91,233). Pada uji regresi logistik multipel, p=0,000 (p<0,05) dengan nilai R2 Nagelkerke sebesar 0,344 atau 34,4%. Usia gestasi dan berat badan lahir berpengaruh bermakna terhadap kematian neonatus, baik secara parsial maupun simultan. Persentase sumbangan pengaruh usia gestasi dan berat badan lahir terhadap kematian neonatus sebesar 34,4%.